The Influence of Physical & Non-Physical Work Environment Towards Perceived Employees Performance - Fitriani, Vida; Pritasari, Adita (Journal of Business and Management, 2019)
Abstract - In this modern era, the development of industry is very advanced and rapid. This matter supported by technological developments increasingly sophisticated so as to facilitate all human work activities. All work activities that exist within the company include producing good and working system arrangements. One of the most important elements to run the goals of a company is human resources. Human resources can affect the effectiveness in generating output as well as driving business. The work environment is one of the most important factors that can affect the physical condition and human psychology. The purpose of this research is to know how does effect of physical and non-physical works environment on employee performance and the most dominant influence between physical work environment and non-physical work environment. The selected research object is an employee of the division of TC&AP PT Pindad Persero Bandung. This is related to the identification of some problems that the employee related to the working environment through interviews. The method used by researchers is multiple linear regressions (MLR). The result of the research shows that the physical work environment is not significant effect on perceived employee performance. The non-physical work environment has significant positively effect on perceived employee performance. Simultaneously the result of work environment variable physical and non-physical has significant effect on employee performance. The results showed that the non-physical work environment had a dominant impact on employee performance of 65.6% compared with the physical work environment variables of 0.34%.Â Keywords: Non-Physical Work Environment, Perceived Employees Performance, Physical Work Environment, Work Environment